Two new species of the genus Neoheterospilus Belokobylskij, 2006 (Hymenoptera: Braconidae: Doryctinae) from Yemen - Belokobylskij, S.a. (Zootaxa, 2020)
Two new species of the genus Neoheterospilus Belokobylskij, 2006, N. (N.) alkowdi sp. nov. and N. (N.) yemenus sp. nov., are described and illustrated from Yemen. An updated key for determination of the Neoheterospilus (Neoheterospilus s. str.) species is provided.